Computer use for work accomplishment: a comparison between nurse managers and staff nurses. - Ngin PM; Simms LM (Journal of Nursing Administration (JONA), 1996)
Studies on computers in nursing typically observed nurses' perceptions toward computers. This study examined the computer use of 528 nurses in three urban teaching hospitals, and compared nurse managers' with staff nurses' time spent at the computer and systems frequently used for work accomplishment. Differences were found in their experiences with computerized information systems (CISs) and expectations of CIS use. Although there was striking similarity in the systems used, nurse managers had significantly greater access to computers and technical support. Findings suggest the importance of integrating clinical and managerial task if unit work is to be accomplished efficiently and effectively.